Bioinspired Scaffold Action Under the Extreme Physiological Conditions of Simulated Space Flights: Osteogenesis Enhancing Under Microgravity - Avitabile, Elisabetta; Fusco, Laura; Minardi, Silvia; Orecchioni, Marco; Zavan, Barbara; Yilmazer, Acelya; Rauner, Martina; Pippia, Proto; Tasciotti, Ennio; Delogu, Lucia Gemma (Frontiers in Bioengineering and Biotechnology, 2020)
Prolonged exposure to microgravity (MG) during long-duration space flights is known to induce severe dysregulation of osteoblast functions connected to a significant bone loss, similar to the condition induced by osteoporosis. Hence, we here present MG as a promising model to challenge the effectiveness of new scaffolds designed for bone regeneration in counteracting bone loss. To this end, we carried out an integrative study aimed to evaluate, in the extreme condition of Random Positioning Machine-simulated MG, the osteoinductive potential of nanocrystalline magnesium-doped hydroxyapatite/type I collagen composite scaffold (MHA/Coll), that we previously demonstrated to be an excellent tool for bone tissue engineering. Initially, to test the osteo-inductivity properties of our bioinspired-scaffold, MHA/Coll structure was fully characterized under MG condition and compared to its static counterpart. Human bone marrow-derived mesenchymanl stem cells were used to investigate the scaffold biocompatibility and ability to promote osteogenic differentiation after long-duration exposure to MG (up to 21 days). The results demonstrate that the nanostructure of MHA/Coll scaffold can alleviate MG-induced osteoblast dysfunction, promoting cell differentiation along the osteogenic lineage, with a consequent reduction in the expression of the surface markers CD29, CD44, and CD90. Moreover, these findings were corroborated by the ability of MHA/Coll to induce the expression of genes linked to osteogenesis, including alkaline phosphatase and osteocalcin. This study confirmed MHA/Coll capabilities in promoting osteogenesis even in extreme long-term condition of MG, suggesting MG as an effective challenging model to apply in future studies to validate the ability of advanced scaffolds to counteract bone loss, facilitating their application in translational Regenerative Medicine and Tissue Engineering.